The Role of Self- Audit for Academic Programmes in Improving Academic Institutisual Performance - Muna Rashed Al- Zayyani (University of Science and Technology, Yemen, 2015)
The overall objective of the study is to outline the impact of educational self evaluation on academic programs performance of higher education institutions through reviewing and analyzing relevant studies and articles.  The study identified higher education institution and their role in achieving utmost development of the society, challenges, factors and elements which necessitates educational self evaluation while striving to improve academic programs. Finally, the study displayed a model comprises elements self evaluation report is based upon. Additionally, suggested recommendations which may direct the endeavors of those involved in carrying out educational self evaluation systems to elevate higher education institutions to achieve excellence and attain accreditation.  Key words: self-educational assessment - academic programs - academic performance - higher education institutions.